The Pressure of the Covid 19 Pandemic, Digitalization, and the Classic Problems of MSMEs in Indonesia - Herispon, Herispon; Anuar, Saiful (ADPEBI International Journal of Business and Social Science, 2023)
This paper attempts to investigate the relationship between the COVID-19 pandemic and the digitalization of Micro, Small and Medium Enterprises (MSMEs), which is still widely discussed in various studies to date in the national economy. Using the method of literature study and descriptive analysis of the data collected. So in this study it can be shown that the covid 19 pandemic has relevance to accelerating the digitization of MSMEs, on the other hand MSMEs have difficulty getting away from problems with capital, location and place of business, business management, inconsistent behavior of MSMEs, marketing and target consumers, massive product innovation, scope simple thinking of MSMEs. The conclusion of the Covid 19 pandemic has accelerated the process of adopting digitalization or online services for MSMEs, so digitalization is crucial, especially during the pandemic